Reactive MnO2 template-assisted synthesis of double-shelled PPy hollow nanotubes to boost microwave absorption. (20th May 2023) - Gu, Huiling; Huang, Ji; Li, Na; Yang, Hua; Chen, Gang; Dong, Chengjun; Gong, Chunhong; Guan, Hongtao
Highlights: Double-shelled PPy hollow nanotubes were synthesized using MnO2 template. The evolution of MnO2 dissolving and the PPy growth was studied. The morphology and reflection loss can be regulated by HCl concentration. The DSH-PPy exhibited a RL min of −50.4 dB and a EAB of 7.7 GHz with a 5 wt.% filling ratio. Abstract: Microwave absorbing materials (MAMs) with wide effective absorption bandwidth (EAB) and low filling ratio are highly desirable for practical applications. Rational design in components and structures is one of the effective strategies to achieve MAMs with high performance. Herein, double-shelled hollow (DSH) polypyrrole (PPy) nanotubes were synthesized with hydrochloric acid (HCl) and sodium p -styrene sulfonate (SS) co-doping polymerization process using manganese dioxide (MnO2 ) nanorods as a self-sacrifice template. With the increase of HCl concentration, the 1D MnO2 core diminishes gradually to form the MnO2 @PPy coaxial nanostructures and finally the DSH PPy nanotube, which tunes the microwave absorption performance. Importantly, the DSH PPy nanotubes exhibit excellent microwave absorption of an optimal reflection loss of –50.4 dB and a wide EAB of 7.7 GHz with a low filling ratio of 5 wt% in a paraffin wax matrix. The excellent microwave absorption is believed to be mainly attributed to the enhanced synergistic effects of interfacial polarization and conduction loss arising from the unique DSH structure and the co-doping polymerization.